PENGARUH KEEFEKTIFAN KOMITE AUDIT DAN KARAKTERISTIK PERUSAHAAN TERHADAP KETEPATAN WAKTU PELAPORAN - Septiayu Kusuma Murdiono Putri; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2015)
This study aimed to examine the effect of audit committee effectiveness and firm characteristics likefinancial condition, size of company, type of auditor and type of industry on the financial reporting lead time as a proxy of the timeliness of reporting. The research was conducted by quantitative methods using secondary data. Secondary data consists of data on the publication date of the financial statements of companies in the IDX website and annual reports of companies listed on the Stock Exchange in year 2013. This research population is company listed on the Indonesian Stock Exchange in year 2013. The procedure of sample selection using purposive sampling method. The number of samples is 277 companies and analysis techniques used are multiple regression. The results showed that the effectiveness of the audit committee, the size of the company, and the type of auditor negatively affect the financial reporting lead time, while the financial condition positive effect the financial reporting lead time. Furthermore, the type of of industry affect the financial reporting lead time.